Pelatihan Untuk Mengembangkan Usaha Trebel Clothing - Prabandari, Wijayanti; Taviprawati, Ervina; Yohanes, Yohanes (Jurnal Pemberdayaan Pariwisata; Vol 6 No 1 (2024): Jurnal Pemberdayaan Pariwisata, 2024)
This activity aims to provide training to TREBEL Clothing owners and employees to create good designs, attractive packaging and marketing promotions via Instagram social media. The method of implementing this activity is by counseling and training. The number of participants in this activity was the owner and 20 employees. Good clothing product design includes the use of color, composition and other design elements, namely choosing the right type of font and using relevant images or illustrations. Attractive packaging includes label design, and the use of branding elements such as logos and slogans. Marketing promotions via Instagram social media include making product posts, short videos, high-quality images, interesting stories, using relevant hashtags. respond to comments, host quizzes or giveaways, and invite followers to share their experiences with TREBEL products. With this new knowledge, TREBEL Clothing owners and employees increased the product's appeal, and achieved success in a competitive market. Keywords: design, packaging, promotion, instagram social medial